MODELLING OF AGRICULTURAL NON-POINT SOURCES POLLUTANTS IN UPPER PANGANI RIVER BASIN (UPRB), TANZANIA - Fredrick, Mwanuzi (Tanzania Journal of Engineering and Technology, 2018)
The Upper Pangani River and its watershed are increasingly being impacted by environmental problems which include non point source pollutants that are threatening the watershed resources. Increased human activities due to population increase, and hence agricultural activities, livestock development, the use of agrochemicals and other land development in the basin, have tended to lead to a serious pollution of the river water which also affects not only the aquatic life but also human health. With intensive and extensive modern agriculture in which artificial fertilizers are in frequent use, there is a high probability to find chemicals easily flowing into water, thus polluting it. The introduction of agricultural chemicals in rivers may be detrimental. Nitrogen and Phosphorus which are present in agricultural chemicals are essential plant nutrients, which when introduced into surface waters may cause some health problems such as blue-baby syndrome and stomach cancer. To carry out this study we divided the Upper Pangani River basin into two sub-basins; Kikuletwa and Ruvu. The study concentrated on Ruvu sub-basin to study and model the pollution transported to the rivers. QUAL2E model was chosen and applied to assess the pollution status of the river network. The model simulated stream flow, dissolved oxygen, phosphorus and nitrogen compounds. From model results, the amount of non-point source load reaching Ruvu river was found to be 7857.81tons/yr for nitrogen and 12057.39 tons/yr for phosphorus. The results of the QUAL2E model suggest that there is pollution at upstream rivers as a result of application of fertilizers to the irrigation schemes which are the main sources of non point source pollution.